The role of knowledge of AI, AR/VR, and the metaverse of higher education students in enhancing students’ business ideation - Puji Prabowo; Iston Dwija Utama; Intan Rahmatillah (Cogent Education)
Recent technology allows the student to generate their business idea more easily, thus this study aims to examine the impact of recent technology such as Artificial Intelligence (AI), Augmented/Virtual Reality (AR/VR), and Metaverse knowledge on business ideation among students. A quantitative approach and purposive sampling method were used by utilizing SmartPLS tools to analyze the 205 valid data we gathered to examine the influences of these students’ knowledge of technologies on entrepreneurial ideation. Our findings reveal that AI knowledge significantly enhances student business ideation rather than AR/VR knowledge. In contrast, knowledge of Metaverse was found insignificant. This research underscores the importance of incorporating AI and AR/VR into higher education curricula to foster innovative student business ideas. Suggestions for future research are embedded in this article.